The Underpricing of Indonesia IPO : Empirical Study on the Firms IPO Listed on Indonesia Stock Exchange 2013-2017 - Laurensia, Winni B1024151020 (Jurnal Manajemen Update, 2019)
ABSTRACTÂ Underpricing is a phenomenon that occurs in most of the IPO share prices on the IDX. Underpricing is avoided by companies because companies do not get maximum funds, on the other hand investors expect underpricing to obtain a large initial return. Underpricing events are important to observe because they involve many factors. The purpose of this study was to determine the effect of Return on Assets (ROA), Financial Leverage, Percentage of Public Offering, Firm Age and underwriter reputation on the level of underpricing. The study was conducted at the IPO companies listed on the IDX in 2013-2017. The total sample of 68 companies used the purposive sampling method. Data is obtained from the prospectus and company financial statements. The analysis technique of this study is using multiple linear regression analysis. Based on the results of the study, it is known that only ROA, Financial Leverage and Underwriter Reputation variables that have the significant effect toward IPO underpricing, otherwise the Percentage of Public Offering and Firm Age.Â Keywords: Underpricing, IPO, IDX, Return on Assets (ROA), financial leverage, percentage of public offering, firm age, underwriter reputationREFERENCESAdams, Thornton and Hall. (2008). IPO Pricing Phenomena: Empirical Evidence Of Behavioral Biases. Journal of Business & Economics Research. Vol 6. No 4Aggarwal, R. & Rivoli, P. (1990). Fads in the initial public offering market? Financial Management, 19(4). 45.Aini, Shoviyah Nur. (2013). Faktor-Faktor Yang Mempengaruhi Underpricing Saham Pada Perusahaan IPO di BEI Periode 2007-2011. Jurnal Ilmiah Manajemen. Vol 1 No 1. Januari 2013Allen, F. & Faulhaber, G.R. (1989). Signaling by underpricing in the IPO market. Journal of Financial Economics, 23, 303-323.Amelia J, Muna dan Yulia Saftiana. (2007). Analisis Faktor-faktor yang Mempengaruhi Underpricing Penawaran Umum Perdana (IPO) di Bursa Efek Jakarta. Akuntabilitas: Jurnal Penelitian dan Pengembangan Akuntansi, Vol 1 No.2 Juli 2007Asrie, S. P. (2018). Faktor-Faktor Yang Memengaruhi Tingkat Underpricing Pada Perusahaan Yang Melakukan Initial Public Offering Di Bursa Efek Indonesia. Jurnal, 1-14Baron, D.P. & Holmstrom, B. (1980). The investment banking contract for new issues under asymmetric information: Delegation and the incentive problem. Journal of Finance, 35, 1115-1138.Baskoro, Gilang dan Moin, Abdul. (2011). Faktor-Faktor Yang Mempengaruhi Underpricing Saham Di Pasar Modal Indonesia. Telaah Bisnis. Vol 12 No 1. Juli 2011Beatty, R.P. 1989. Auditor Reputation and The Pricing of Initial Public Offerings. The Accounting Review, 64(4), pp: 693-707.Benveniste, L.M. & Spindt, P.A. (1989). How investment bankers determine the offer price and allocation of new issues. Journal of Financial Economics, 24, 343-361.Bruton. M. J. (1985). Introduction to Transportation Planning. Melbourne: Hutchinson.Chod, J. (2010). Strategic IPOs and product market competition. Boston: ScienceDirect.Creswell, J. W., 2003. Research Design Qualitative, Quantitative, and Mixed Methods Approach. 2nd ed. United States: Sage Publications.Croes, L. (2017). IPO Underpricing in the US The impact of Information Asymmetry on Todayâ€™s IPO Market. Journal, 2-38Daljono. (2000). Analisa Faktor-Faktor yang Mempengaruhi Initial Return Saham yang Listing di BEJ Tahun 1990-1997. Makalah Seminar, Seminar Nasional Akuntansi IIIDonaldson, M. W. (2015). Examining the Relationship between Selected Examining the Relationship between Selected. Walden Dissertations and Doctoral Studies, 112.Emilia, Lucky Sulaiman, dan Roy Sembel. 2008. Faktor â€“ Faktor yang Mempengaruhi Initial Return 1 Hari, Return 1 Bulan, dan Pengaruh terhadap Return 1 Tahun Setelah IPO. Journal of Applied Finance and Accounting, 1(1), pp: 116-140.FAWCETT, J. C. (2006). Initial Public Offerings: An Analysis of Theory and Practice. The Journal Of Finance, 399-437.Ghozali dan Mansur. (2002). Analisis FaktorFaktor Yang Mempengaruhi Tingkat Underpriced Di Bursa Efek Jakarta. Jurnal Bisnis dan Akuntansi. Vol 4 No 1. April 2002Gumanti, T.A., Earning Management Dalam Penawaran Pasar Perdana Di Bursa Efek Jakarta, Artikel Ilmiah Dipresentasikan Dalam Simposium Nasional Akuntansi III, Jakarta, 2000.Gusti Ayu Sri Kartika, I. M. (2017). Faktor-Faktor Underpricing Initial Public Offering Di Bursa Efek Indonesia. E-Jurnal Akuntansi Universitas Udayana, 2205-2233.Haghiri, A., & Haghiri, S. (2012). The investigation of effective factors on stock return with emphasis on ROA and ROE ratios in Tehran stock exchange (TSE). Journal of Basic and Applied Scientific Research, 2, 9097-9103. Retrieved from http://textroad.com/Basic%20and%20Applied%20Scientific%20Resear hScope. tmlHajek, P., Olej, V., & Myskova, R. (2013). Forecasting stock prices using sentiment information in annual reports-a neural network and support vector regression approach. WSEAS Transactions on Business and Economics, 10(4), 293-305. Retrieved from http://www.wseas.org/multimedia/journals/economics/2013 /235702-202.pdfHANDAYANI, S. R. (2008). Analisis Faktor-Faktor Yang Mempengaruhi Underpricing Pada Penawaran Umum Perdana (Studi Kasus Pada Perusahaan Keuangan yang Go Publik di Bursa Efek Jakarta Tahun 2000-2006). Semarang: Sri Retno Handayani.H, D. A. (2016). Analisis Faktor â€“ Faktor Yang Mempengaruhi Underpricing Saat Initial Public Offering Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2014. Jurnal, 1-20.How and Yeo. (2000). The pricing of underwriting services in the Australian capital market. Pasific- Basin Finance Journal. Vol 8Hyde, K., 2000. Recognising Deductive Processes in Qualitative Research. Qualitative Market Research: An International Journal, Volume 3, pp. 82-89.Ibbotson, R.G. & Ritter, J.R. (1995). Initial Public Offerings, in: Finance (R.A.Jarrow, V. MaksimoviÂ¸c, and W.T. Ziemba, Eds.) pp. 993-1016. Elsevier, Amsterdam.Islam, M. A. (2010). An Empirical Investigation of the Underpricing of Initial Public Offerings in the Chittagong Stock Exchange. International Journal of Economics and Finance, 4-15.Jerry Coakley, N. I. (2005). Testing the Winner's Curse Hypothesis: Evidence from IPOs in China. China: https://www.researchgate.net/publication/256066569.Kim, Keneth, A. and Hyun Shan Shin. (2001). The Underpricing of Seasoned Equity Offerings: 1983-1998. Available from: URL: http://www.ssrn.com.Leibenstein, H. (1950). Bandwagon, Snob, and Veblen Effects in the Theory of Consumers' Demand. The Quarterly Journal of Economics, 183-207.Lind, D. A., Marchal, W. G. & Wathen, S. A., 2004. Statistical Techniques in Business & Economics. 12th ed. New York: McGraw-Hill/Irwin.Loo, Lee and Yi. (1999). Profitability and Volatility of IPO Firms and Underwriter Reputation. International Journal Of Business. Vol 4. No 2Loughran, T. & Ritter, J.R. (2004). Why has IPO underpricing changed over time? Financial Management, 33, 5-37.Mahyani, P. &. (2016). Factors determining IPO Underpricing in Indonesia. FOKUS MANAJERIAL, 67-76.Martini, D. M., & Rahfiani, K. (2009). The effect of financial ratios, firm size and cash flow from operating activities in the interim report to the stock return. Chinese Business Review, 8(6), 44-55. Retrieved from http://www.chinabusinessreview.com/Mauer, D. C. & Senbet, L.W. (1992). The Effect of the Secondary Market on the Pricing of Initial Public Offerings: Theory and Evidence. Journal of Financial and Quantitative Analysis, 24, 55-79.Maxwell, A. (2014). Bandwagon effect and network externalities in market demand. Asian Journal Of Management Research, 527-533.Megginson, W.L., & Weiss, K.A. (1991). Venture capitalist certification in initial public offerings. Journal of Finance, 46, 879-903.McManus, P. A., 2011. Introduction to Regression Model for Panel Data Analysis. Indiana: Indiana University.Michaely, R., & Shaw, W. H. (1994). The pricing of initial public offerings: Tests of adverse-selection and signalling theories. The Review of Financial Studies, 7(2), 279-319.Mirrless, J.A. (1999). The theory of moral hazard and unobservable behaviour: Part I, Review of Economic Studies, 66: 3-21.Mishra, A. K. (2012). Underpricing of initial public offerings in India. India: Investment Management and Financial Innovations.Mukhlis, M Zainul. (2012). Pengaruh Underpricing Pada Penawaran Saham Perdana Di Bursa Efek Indonesia Tahun 2008-2010. Jurnal Ekonomi Muda Kreatif. Vol 1 No1Nachrowi, N. D. & Usman, H., 2002. Penggunaan Teknik Ekonometri. Jakarta: PT RajaGrafindo Persada.Nakhaei, H., Abdul Hamid, N., & Anuar, M. (2013). Evaluation of company performance with accounting and economic criteria in Bursa Malaysia. Journal of Global Business & Economics, 6, 49-62. Retrieved from http://www.globalresearch.com .myNewbold, P., Carlson, W. L. & Thorne, B. M., 2003. Statistics for Business and Economics. 5th ed. New Jersey: Pearson Education.Pahlevi, R. W. (2014). Analisis Faktor-Faktor Yang Mempengaruhi Underpricing Saham Pada Penawaran Saham Perdana Di Bursa Efek Indonesia. Jurnal Siasat Bisnis, 219-232.Panahian, H., & Akbarzadeh, H. (2010). Determination and evaluation of privatization effects on financial performance of firms in Tehran stock exchange (TSE). American Journal of Applied Sciences, 7, 597-602. Retrieved from http://thescipub.com/ajas.tocPettit, R. & Singer, R., 1985. Small Business Finance: A Research Agenda. Financial Management, Vol. 14 No. 3, pp. 47-60.Philip J. Lee, S. L. (1996). Australian IPO pricing in the short and long run. Journal of Banking & Finance, 1189-1210.Puspaningsih dan Mujib. (2011). Analisis Faktor-Faktor Yang Mempengaruhi Underpricing Pada Perusahaan Go Public Di Bursa Efek Indonesia. Aplikasi Bisnis. Vol 10 No 9. Maret 2011Ritter, Jay R., and Ivo Welch .(1991) .A review of IPO activity, pricing, and all ocations. Journal of Finance 57, 1795-1828.Rock, K. (1986). Why New Issue are Under Priced. Journal of Financial Economics, 15, 187-212.Rohit Bansal, A. K. (2012). Determinants of IPOs Initial Return: Extreme Analysis of Indian Market. Journal of Financial Risk Management, 68-74.Sari, A. M. (2015). Analisis Faktor- Faktor Yang Mempengaruhi Tingkat Underpricing Pada Saat Initial Public Offering (Ipo) Di Bursa Efek Indonesia Periode 2010-2014. E-Proceeding Of Management, 1589.Saunders, M., Lewis, P. & Thornhill, A., 2009. Research Methods for Business Students. 5th ed. England: Pearson Education.Sharma and Seraphim. (2010). The Relationship between IPO Underpricing Phenomenon & the Underwriterâ€™s Reputation. The Romanian Economic Journal. Vol 38Setianingrum dan Suwito. (2008). FaktorFaktor Yang Mempengaruhi Tingkat Underpricing Pada Perusahaan Yang Go Publik Di Bursa Efek Jakartaâ€ (Studi Empiris Pada Perusahaan Yang Melakukan Listing di BEJ tahun 2001- 2004). Fokus Manajerial. Vol 6 No 1. Januari 2008Sher, C.-Y. (2011). Distinguishing Strategic Voting from Bandwagon Effects â€“ How did Voters' Subjective Expectations Affect Results. 1-30.Suad Husnan, M. M. (2014). Price Stabilization And Ipo Underpricing: An Empirical Study In The Indonesian Stock Exchange. Journal Of Indonesian Economy and Business, 129 â€“ 141.Tinic, S.M. (1998). Anatomy of IPOs of Common Stock. The Journal of Finance, 43(4). 789-822.Vong, A. P. (2009). An empirical extension of Rockâ€™s IPO underpricing model to three distinct groups of investors. Applied Financial Economics, 1257â€“1268.Wenlian, Ng, L., Zhang, B. & Zhu, F., 2012. Information Asymmetry and Capital Structure Around the World. pp. 1-43.Welch, I. (1989). Seasoned Offerings, Imitation Costs, and the Underpricing of Initial Public Offerings. Journal of Finance, 44, 421-449.Widhiastina, P. (2016). Pengaruh Return On Asset, Financial Leverage, Dan Ukuran Perusahaan Terhadapunderpricing Pada Perusahaan Yang Melakukan Initial Public Offering (Ipo) Di Bursaefek Indonesia. Jurnal Ilmiah Wahana Akuntansi, 2Wilson, J., 2013. Essentials of Business Research: A Guide to Doing Your Research Project. In: Los Angeles: SAGE.Witjaksono, Lydia Soeryadjaya. (2012). Analisis Faktorâ€“ Faktor Keuangan Yang Mempengaruhi Fenomena Underpricing Pada Perusahaan Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia 2002-2010. Berkala Ilmiah Mahasiswa Akuntansi. Vol 1 No 1. Januari 2012Yasa, Gerianta Wirawan. (2008). Penyebab Underpricing pada Penawaran Saham Perdana di Bursa Efek Jakarta. Jurnal Akuntansi Bisnis. Vol 3Yolana, Chastina dan Dwi Martani. (2005). Variabel-Variabel yang Mempengaruhi Fenomena Underpricing pada Penawaran Saham Perdana di BEJ tahun 1994- 2001, Simposium Nasional Akutansi VII Solo, 15-16 September 2005YONG, O. (2013). Winner's Curse, Size Effect and Bandwagon Effect in Explaining the Under-Pricing Phenomenon of Malaysian Ipos. CREAM - Current Research in Malaysia, 101-120.Yustisia dan Roza. (2012). Faktor-Faktor Yang Mempengaruhi Tingkat Underpricing Saham Perdana Pada Perusahaan Non Keuangan Go Public. Media Riset Akuntansi . Vol 2 No 2Zarafat, H. (2014). The Long-Term Performance of Initial Public Offerings: Evidence from Bursa Malaysia. Malaysia: Journal of Applied Economics and Business Research.Zikmund, W. G., Babin, B. J., Carr, J. C. & Griffin, M., 2010. Business Research Methods. 8th ed. United States: South-Western College.Zulkarnaen, A. (2014). Analisis Faktor-Faktor Yang Mempengaruhi Underpricing Saham Saat Initial Public Offering (Ipo) Di Bei (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2010- 2014). Jurusan Akuntansi, 1-15Â